Pengembangan Aplikasi Berbasis Web Di SMK Pustek Serpong Dengan Menggunakan Model Waterfall - Azis Firmansyah; Muhamad sahrul; Muhammad fathin fadhil; Aries Saifudin (CV. Multi Kreasi Media, 2023)
In this research, Pustek Serpong Vocational High School has a background problem in the learning process. At Serpong Pustek Vocational School it uses the old method and is still limited in the delivery of material provided by the teacher. In dealing with this, an e-learning application was developed with a waterfall web-based system. This Waterfall system uses a simple method. This method is divided into 2 stages, namely the output stage and the input stage. This research was carried out by collecting data by interviewing sources directly, the design of the e-learning application was made with UI/Design. This e-learning application is made with the PHP programming language, and has passed several tests by the developers. Within a few months developers maintain this application to find out bugs or errors and carry out further development.